Neuroprotective effect of edible bird’s nest in chronic cerebral hypoperfusion-induced neurodegeneration in rats - Ismaeil, Rehab A.; Ahmad Affandi, Khairunisa; Chua, Kien Hui; Alallam, Batoul; Mohamed, Wael Mohamed Yousef; Mohd Noor, Mohd Fadly (2021)
Vascular dementia (VD) is the second most prevalence type of dementia after Alzheimer’s disease (AD). It is marked by insufficient blood supply to the brain leads to progressive loss of memory and cognitive skills. Continuous reduction in cerebral blood flow, which made by chronic cerebral hypoperfusion, leads to overproduction of reactive oxygen species together with reduction in glucose and oxygen that cause cognitive decline. Until now there is no available curative treatment for VD and the only available option is symptomatic treatment. Several studies have shown that recent alternative medicines have underscored the neuroprotective and antioxidant ability of the edible bird’s nest (EBN). Nevertheless, there has been minimum studies explored the effect of EBN in reducing the risk of VD. The current study evaluates the effects of EBN on hippocampal neurons mainly in CA1 hippocampal region in chronic cerebral hypoperfusion rat model. Chronic cerebral hypoperfusion model was created by permanent occlusion of bilateral common carotid arteries (2VO) in rats that induced inflammation in neuronal cells. The rats were divided into 4 groups: A) Sham group, B) 2VO group, and Groups C and D are 2VO rats treated with 2 different doses of oral EBN. After 8 weeks, the rats were killed and the hippocampi were examined histopathologically by counting the viable neuronal cells and the level of F2 Isoprostane, an oxidative stress indicator, was measured. The results showed significant reduction in the neuronal cell death and significant decline in F2 Isoprostane in the group of rats treated with EBN. This is the first study that links the neuroprotective effects of EBN in the prevention of dementia related to AD. The results will have a great impact in delaying the progression of dementia in AD patients.